Effects of gender roles and attitudes on showing love in marriage - Jugović, Ivana (Array, 2011)
Our aim was to examine the effects of love, gender roles and attitudes toward gender roles on performing household tasks and showing love in marriage. We expected that individuals who love their spouses more would show love more and divide household tasks more equally than individuals who love their spouses less. Regarding gender roles, we expected that men and women who are expressive (i.e. have feminine or androgynous gender roles) would show love more than men and women low in expressivity (i.e. the ones with masculine role). It was also expected that individuals from couples with traditional attitudes toward gender roles would perform more gender stereotypical household tasks (women more routine and men more occasional household chores) than individuals from couples with egalitarian attitudes who would divide household tasks more equally. We tested 302 married couples from Croatia and 351 married couples from Serbia of different ages (20-82 years) and various urban/rural backgrounds. Length of marriage varied between one month and 57 years. We administered the Love Scale (Braiker and Kelly, 1979), Personal Attributes Questionnaire (PAQ ; Spence, Helmreich & Stapp, 1975) and Attitudes toward Gender Roles Scale (Kamenov, Jugović & Jelić, 2009). Scales for measuring dependent variables were Doing Housework Scale which has two subscales (Routine chores and Occasional chores) and the Ways of Showing Love Scale which measures 6 factors (Communal Orientation/Sacrifice, Emotional Openness and Support, Physical Affection, Verbal Affection/Gifting, Domestic Instrumentality, and Public Instrumentality).As hypothesized, results showed that love has positive effects on showing love for both men and women. When it comes to household chores, love has effects only on the routine household chores and not on the occasional chores: men who love their spouses more are more engaged in doing routine chores. Gender roles do not have a statistically significant effect on doing housework, but do on showing love. As expected, men with higher expressivity show love more than men with stereotypically masculine role. Attitudes toward gender roles have a statistically significant effect on performing routine household tasks by men, but not by women. In line with our hypothesis, men from couples in which both partners hold egalitarian attitudes perform routine household chores more than men from couples in which both partners hold traditional attitudes toward gender roles. Although love had the most pervasive effect, results suggest that gender roles and attitudes toward gender roles should also be considered when explaining showing love in married couples and the division of routine household chores between spouses. It also seems that gender roles and attitudes toward gender roles effected men's performance of routine household chores and showing love more than women's. Along with these overall results, specific results obtained in Croatian and Serbian samples will be discussed.